Contributions to the development of programs for the gifted within the educacional environment - Blumen, Sheyla (1995)
A number of students in our schools possess learning abilities and specialized talents to such degree that their educational needs cannot be met in a regular school program. Special educational programs for the gifted and talented are an essential part of any school program which recognizes and respects individual differences among its pupils. The philosophy which guides our proposal is based on the belief that: (1) each child is a unique human being who possesses individual educational needs and abilities; and (2) it is the responsibility of our schools, first to identify those needs and abilities and then, to provide the educational experiences for meeting individual needs and developing each child's abilities to the fullest degree.